Biological sex influences psychological aspects of the biopsychosocial model related to chronic pain intensity and interference among South Korean patients with chronic secondary musculoskeletal pain in rheumatic diseases - Kim, Hee Jun; Meeker, Timothy J.; Jung, Ju-Yang; Kim, Ji-Won; Kim, Hyoun-Ah (Frontiers in Psychology, 2023)
Introduction Pain is a prominent contributor to negative personal and social outcomes, including increased disability and mortality, in many rheumatic diseases. In the Biopsychosocial model of chronic pain, psychological and social factors share roles with the biology of the injury in determining each patient’s pain and suffering. The current study explored factors associated with clinical pain intensity and interference among patients with chronic secondary musculoskeletal pain in rheumatic diseases. Methods In total, 220 patients experiencing chronic secondary musculoskeletal pain participated. Biological factors (age, biological sex, pain condition, pain duration, pain sensitivity, and comorbidity), socio-economic factors, psychological factors (pain catastrophizing and depressive symptoms), and pain intensity and interference were measured. Descriptive, multivariable linear regression and partial correlation analyses were conducted. Subgroup analysis by sex was conducted to examine differences in how different factors affect the pain experience. Results The mean age of the participants was 52.3 years (SD = 12.07) and ranged from 22 to 78. Average pain intensity was 3.01 (0–10 scale) and average total pain interference score was 21.07 (0–70 scale). Partial correlation found positive correlations between pain intensity and interference with depression (intensity: R = 0.224; p = 0.0011; interference: R = 0.351; p < 0.001) and pain catastrophizing (intensity: R = 0.520; p < 0.001; interference: R = 0.464; p < 0.001). In males, pain condition (β = −0.249, p = 0.032) and pain catastrophizing (R = 0.480, p < 0.001) were associated with pain intensity. In males, the simple correlation between pain intensity and depression (R = 0.519; p < 0.001) was driven by pain catastrophizing. In females, pain catastrophizing (R = 0.536, p < 0.001) and depressive symptoms (R = 0.228, p = 0.0077) were independently associated with pain intensity. Age (β = −0.251, p = 0.042) and pain catastrophizing (R = 0.609, p < 0.001) were associated with pain interference in males, while depressive symptoms (R = 0.439, p < 0.001) and pain catastrophizing (R = 0.403, p < 0.001) were associated with pain interference in females. Again, in males, the simple correlation between pain interference and depression (R = 0.455; p < 0.001) was driven by pain catastrophizing. Discussion In this study, females were more directly affected by depressive symptoms than males, regarding pain intensity and interference. Pain catastrophizing was a significant factor influencing chronic pain for both males and females. Based on these findings, a sex-specific approach to the Biopsychosocial model should be considered in understanding and managing pain among Asians with chronic secondary musculoskeletal pain.